Sąd Parysa. Widowisko pantomimiczne (w relacji filozoficznego osła) - Wasyl , Anna Maria (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2020)
This paper focuses on the description of a pantomimic spectacle given by Apuleius in the 10th book of his Metamorphoses. Set in a theater in Corinth and narrated by Lucius the ass, this performance relates the story of the judgment of Paris. Lucius, as the viewer of the performance (and, from our perspective, its main teller), styles himself as an objective ‘connoisseur’ of the art of pantomime. Upon a closer look, however, one realizes that he has been absorbed by the scenic illusion and takes it for his own reality. Consequently, despite his penchant for philosophizing, he turns out to be not merely Lucius the ass, but an asinine philosopher, indeed.